ChemInform Abstract: Oxidative Rearrangement via in situ Generated N‐Chloroamine: Synthesis of Fused Tetrahydroisoquinolines. Issue 30 (July 2016) - Murai, Kenichi; Matsuura, Kei; Aoyama, Hiroshi; Fujioka, Hiromichi
Abstract: A series of spiro‐tetrahydroisoquinoline substrates is transformed to the heterocyclic title scaffold via N‐chloroamines, generated in situ (mechanism).